The Impact of Generation on Nurse Manager Job Satisfaction. Issue 7 (July 2022) - Keith, Angela C.; Warshawsky, Nora; Neff, Donna; Loerzel, Victoria; Parchment, Joy; Grandfield, Elizabeth
Abstract : OBJECTIVE: The aim of this study was to determine the effects of generational membership on nurse managers' (NMs') perception of their practice environment and job satisfaction using the Nurse Manager Practice Environment Scale (NMPES). BACKGROUND: Boomers, Generation Xers, and millennials make up the NM workforce. Each has specific perceptions and expectations for their practice environment and job satisfaction. Little is known about these differences. METHODS: A secondary analysis of NM survey data was conducted using descriptive statistics and multiple regression to identify the impact of generation on NMs' perception of their practice environment and satisfaction. RESULTS: Generational membership did not significantly impact NMPES or job satisfaction scores, but the practice environment was a strong predictor of these outcomes. CONCLUSION: Generational membership did not impact NMs' satisfaction for this sample, but the practice environment did. Further research is needed to examine additional factors that influence NM satisfaction and retention.